Pertumbuhan dan percepatan molting kepiting bakau (Scylla serrata) yang diberi ekstrak temu kunci (Boesenbergia pandurata) 3 In 1 BIOIMUN® di tambak silvofishery Desa Salo Palai Kecamatan Muara Badak Kabupaten Kutai Kartanegara: The growth and accelerate molt of mud crab (Scylla serrata) given Boesenbergia pandurata extract in silvofishery ponds Salo Palai Village Muara Badak District Kutai Karanegara Regency - Jolpano, Andre; Handayani, Esti; Saptiani, Gina (Nusantara Tropical Fisheries Science (Ilmu Perikanan Tropis Nusantara), 2023)
This research aimed to study the administrasion of B. pandurata extract mixed with crab feed on the percentage of molting, growth, and survival, and feed conversion ratio of mud crabs reared in silvofishery ponds. This research was conducted in Salo Palai Village, Muara Badak District, Kutai Kartanegara Regency. This study used a completely randomized design, with 4 treatments and 3 replications. The extract of B. pandurata in the form 3 In BIOIMUN® drug there are 4 treatment dose dasnamely (0 mL/kg, 20 mL/kg, 25 mL/kg, 30 mL/kg feed). The crabs used came from the catch of the Muara Badak community with a size of 200-280 g, and were culture for 4 weeks (30 days). The crabs were fed fresh fish with the addition of extract 2 times a day, in the morning (07.00-08.00) and afternoon (16.00-17.00), but feeding was done every 2 days. The feed given was weighed as much as 5% of the weight of the crab. The results showed that the administration of 3 In 1 BIOIMUN® in treatment P1 (20 mL/kg) affect the percentage of molting, growth, survival, and feed conversion ratio.